PEMBERDAYAAN UMKM DAN TATA KELOLA DESTINASI PARIWISATA UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT DI MASA PANDEMI COVID-19 DI NUSA PENIDA, KABUPATEN KLUNGKUNG, BALI - Putu Herny Susanti; Ni Luh Sriasih (UNHI Press, 2021)
Nusa Penida is a tourist destination that has begun to be recognized by tourists and is a favorite destination for foreign tourists who have also been affected by the Covid-19 pandemic.The existence of tourists in Nusa Penida is a place for entrepreneurs and small communities to depend on their lives. In the situation of the new era of life in the midst of the Covid-19 pandemic, various efforts are being made by the government and the community to survive in this very difficult situation.Community service through the real work lecture program from the University of Hindu Indonesia is expected to help the community in economic recovery and the revival of the tourism service industry sector. The development of micro, small and medium enterprises, as well as the management of tourism destinations in the new era of the pandemic, is expected to generate tourism. Collaboration of activities by KKN students in empowering UMKM through fostering small businesses owned by residents affected by the pandemic, in this case the traditional jaje bali culinary business, both in raw material selection, production processes, packaging, marketing, promotion and training in simple financial book. Tourist destination management assistance is carried out through the presentation of material on the management of tourist destinations during the Covid-19 pandemic so that they can immediately rise up and increase the income of people who depend on the tourism service industry sector. Health protocols to enjoy tourist destinations in the new era must be strictly implemented, namely social distancing, washing hands and measuring body temperature when entering tourist attractions and accommodation and still wearing a mask. This is done to increase public and tourists' trust in tourist destinations in Nusa Penida.